Effects of replacement of alfalfa by big-leaf mulberry on growth performance, digestion and meat quality in growing rabbits - Zhuang Xue Wu; Long Pei Yang; Hua Xiu Gao; Guo Zhi Wen; Fa Si Dai; Xia Ming Zhu; Xin Li Wang (World Rabbit Science, 2019)
This study aimed to investigate the effect of sundried big-leaf mulberry (BLM) as a replacement for alfalfa on the growth performance, digestibility of nutrients, nitrogen (N) utilisation and meat quality in New Zealand White rabbits. One hundred and sixty weaned rabbits, aged 35±1 d and with a body weight of 755±26 g, were randomly assigned to the 4 treatments with 20 replicates of 2 rabbits (1 male and 1 female) each. Animal performance was evaluated between the 35th and 77th d of age in 40 animals per treatment. The coefficients of total tract apparent digestibility (CTTAD) of nutrients and N utilisation were measured between 77 to 83 d of age in 30 animals per treatment. The control rabbits were fed a corn-soybean meal-alfalfa meal based diet. The three experimental groups were fed a similar diet in which the alfalfa meal was replaced by 10% (BLM10), 20% (BLM20), or 30% (BLM30) BLM. The final body weights and average daily gain were higher (P<0.05) in BLM20 rabbits compared to control and BLM30 rabbits. Although BLM inclusion had no effects on the CTTAD of dry matter, organic matter and crude protein (P>0.10), the CTTAD of ether extract was higher in rabbits fed the diets based on BLM (P<0.05). No effect of treatment was noted on ingested and faecal N. Urinary (P<0.05) and retained N (P<0.10) were higher in animals fed with BLM30 and BLM20 diets, respectively. Dietary BLM supplementation increased a* (P<0.05) and tended to reduce L* (P<0.10) in rabbit meat samples. It was concluded that replacing alfalfa meal with BLM (20%) can promote growth and increase ether extract digestibility. Additionally, dietary BLM supplementation can increase the redness value of meat.